EFFECTIVENESS OF DEVELOPMENT LEARNING MEDIA USING ELECTROCARDIOGRAMS (ECG) IN ELECTRICITY AND MAGNETIC LECTURES - Fasih Bintang Ilhami; Mohammad Budiyanto (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2022)
Learning creative media can expedite and increase the efficiency of learning to lead to goals of learning that can be achieved owing to delivering easy message technology for learning purposes. This study aims to find out the effective development of learning media using electrocardiograms (ECG) in electricity and magnetic lectures. The population of this study was used students in electricity and magnetic lectures with a total of students 20 and samples were by purposive sampling technique. Data collection techniques used were questionnaires with pre-test and post-test and conducted by statistical analysis Paired t-test. The average score of students before being taught using learning media using ECG is 6.65 and significantly increases to 8.40 after being given a learning media using ECG. The effectiveness analysis of learning media using ECG by Paired t-test showed there is a significant difference between before and after being taught using learning media compared to before learning creative lectures with results ?=0.000 < 0.05. Therefore, the development of learning creative media using ECG in electricity and magnetic lectures increasing of student knowledge which is fundamental considering utilize of ECG for possibly early detection of heart problems